(3JeKGd GdCeKGds - (3GdTjHj , eMeO Hf Ydj Hf eMeO Hf CHj HcQ GdbQTj Gdecj GdTGaYj GdYHOQj, LeGd GdOjf CHh GdeMGSf,J (B837 (3g` s
(3ChdgG (B:s
(3hHYO (B: (3agPg CeKGd djS dgG eKGd hahGFO cGdLhGgQ haQGFO cGdBd s
(3BNQgG (B:s
(3ai TQM GdeKd (B" (3jhe Hjhe GdMaU GdeLhQ (B" (3ahKHhG Ydi Yege aLhQhG HjJg aTcG Pdc Edi CNjg heKdg VQH jVQH s
(3QJHg eUfag Ydi MQha GdeYLe hTQM hTQM cd eKd hGSJbUi eG bGdg GdSGHbhf Ydjg ajgs
(3hcJHJ GdCHhGH hGdCeKGd HGdMeQI s
(3hYdi GdfSNI JedcGJ HYVgG ZjQ eDQN hHYVgG eMOK s
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdCOHs